Diversity And Distribution Of Pteriidae (Mollusca: Bivalvia) In Malaysian Waters - Cheah, Wee (2017)
A study on the diversity and distribution of Pteriidae oysters in Malaysian waters has been conducted at 9 locations which covered the Straits of Malacca (6 locations}, the South China Sea (2 locations} and the Sulawesi Sea (1 location). A total of 12 species of pteriids from two genera were identified with 7 species from the genus Pinctada, namely, P. albina, P. chemnitzii, P. fucata, P. maculata, P. margaritifera, P. maxima, and P. nigra while 5 species from the genus Pteria, namely, P. avicular, P. brevialata, P. contumix, P. loveni, and P. penguin. Of these, nine species are first time recorded in Malaysian waters. Combination of twelve shell characters and morphometric measurement were found to be useful in the identification of Pteriidae oyster up to species level but only restricted to well-preserved shells that not differed much from its original shapes.